2019
DOI: 10.1002/aoc.5064
|View full text |Cite
|
Sign up to set email alerts
|

A modern approach for the sensing of aqueous Al(III) ion by Ni(II) Salen‐type Schiff base complexes

Abstract: In this work, we explore a modern concept of transmetalation (metal exchange) for the effective recognition of aqueous Al(III) ion. Three different Ni(II) salen‐type Schiff base complexes with different spacer diimine groups were prepared for the metal exchange reaction. These probes recognize Al(III) both colorimetically as well as fluorimetrically. The efficiency in sensing is mainly due to the low emission characteristics of the respective Ni(II) complexes which results in enhanced emission on the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…This stability has been demonstrated by N. Mohan et al, who reported on a fluorescent probe based on Ni(II)-salen (1). This probe enables the detection of metallic analytes such as Al(III) through a transmetalation process [18]. Similarly, J. Yu et al developed a turn-off-on fluorescence chemosensor utilizing an Fe(III)-salen complex (2), which exhibits a redox response for the detection of hydrazine [19].…”
Section: Introductionmentioning
confidence: 99%
“…This stability has been demonstrated by N. Mohan et al, who reported on a fluorescent probe based on Ni(II)-salen (1). This probe enables the detection of metallic analytes such as Al(III) through a transmetalation process [18]. Similarly, J. Yu et al developed a turn-off-on fluorescence chemosensor utilizing an Fe(III)-salen complex (2), which exhibits a redox response for the detection of hydrazine [19].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-based complexes for aluminum ion detection are not widely reported in the literature, as metalated complexes may undergo trans-metalation. However, such complexes can exhibit not only effective aluminum sensing properties but also function as aluminum ion removers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because the molecular central position contains four coordination atoms of O, N, N, and O, which can be used as a good ligand for certain metals, they were widely applied to materials, [1,2] catalysis, [3][4][5][6][7] biomedicine, [8][9][10] and other fields. [11,12] For example, Zhang et al [1] provided a comprehensive introduction for many salen-type Schiff bases metal complexes, to be used as soluble conjugated materials, as converters for light/electricity signals in organic light-emitting diodes and dye-sensitized solar cells, energy storage, and potential conductive thermoelectric materials. He pointed out that metal Schiff base chemistry can and will make important contribution to the global energy problem.…”
Section: Introductionmentioning
confidence: 99%